Pengaruh Konsentrasi Suspensi Cu-zeolit Alam Aktif dalam Akuades terhadap Daya Antimikroba pada Candida albicans - Nabilah Aulia Putri; Dyah Irnawati; Purwanto Agustiono (Jurnal Material Kedokteran Gigi, 2018)
Activated Cu-natural zeolite is an antimicrobial agent (fungicide) combination of copper and carrier agent activated natural zeolite. The aim of this study was to determine the effect of concentration of activated Cunatural zeolitesuspension in aquadest on antimicrobial activity in C albicans. Materials used were natural zeolite (Wonosari), 2 M HCl solution, CuCl2.2H O powder (Merck, Germany), cultured C. albicans, and Sabouraud agar (Merck, Germany). Natural zeolite (50 g) was activated with500 mL 2 M HCl (1 hour/100o C). Activated natural zeolite was reacted with 250 mL 0.2 M CuCl2 (1 hour/100 C). Cu-natural zeolite suspension in aquadest were divided to 3 groups (9 mg/mL, 18 mg/mL, and 36 mg/mL) (n=4). The suspensionwas contacted with C. albicans(120 minutes), diluted, grown on Sabouraud agar, then incubated (48 hours/37oC). The colonies was countedin CFU/mL. Data were analyzed with one way ANOVA test (a = 0,05) and LSD The mean and standard deviation were 36.800 6.453 (9 mg/mL), 31.675 6.445 (18 mg/mL), and 22.375 3.025 (36 mg/mL) (CFU/mL). The result of one way ANOVA test showed that there is influence of the concentration of the suspension to antimicrobial activity in C. albicans (p<0,05). The result of LSD0,05 test showed significant differences between the concentration 36 mg/mL with 9 mg/mL and 18 mg/mL (p<0,05). High concentration of activated Cu-natural zeolite could increase its antimicrobial activity against C. albicans.